Do Islamicity Performance and Green Banking Improve Islamic Bank Stability in Indonesia? - Ahmad Fauzul Hakim Hasibuan; Syawal Harianto; Syahru Liza Putri Akmal (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
Islamic banking has increasingly emphasized the integration of Sharia compliance and sustainability practices as part of its long-term resilience strategy. However, empirical evidence regarding the relationship between Islamicity-based performance, Green Banking, and bank stability remains inconclusive, particularly in emerging Islamic financial systems such as Indonesia. This study investigates the influence of Islamicity Performance Index (IPI) components and Green Banking practices on the stability of Islamic banks in Indonesia during the 2021–2024 period. Using balanced panel data from Islamic commercial banks, the study examines five IPI dimensions, namely Profit-Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), Directors–Employees Welfare Ratio (DEWR), and Islamic Income versus Non-Islamic Income Ratio (IsIR). Moderated Regression Analysis (MRA) with pooled panel estimation and HC3 robust standard errors was employed to evaluate both direct and moderating effects. The findings reveal that only IsIR demonstrates a consistent positive and significant effect on bank stability, indicating that income purity remains the primary source of resilience in Islamic banking institutions. Meanwhile, PSR, ZPR, EDR, and DEWR do not show significant direct effects, suggesting that distributive justice, welfare orientation, and risk-sharing mechanisms have not yet translated into measurable short-term stability outcomes. In addition, Green Banking does not moderate any relationship between IPI indicators and bank stability, implying that sustainability initiatives still operate separately from core Sharia performance systems. These findings contribute to stakeholder theory, maqāṣid al-sharīʿah, and sustainability theory by highlighting the limited institutional integration of ethical, social, and environmental governance within Islamic banking. The study emphasizes the importance of strengthening integrated Sharia–ESG governance, enhancing risk-sharing financing structures, and embedding sustainability considerations into banking operations and strategic decision-making. ABSTRAK - Apakah Kinerja Islamicity dan Green Banking Meningkatkan Stabilitas Bank Syariah di Indonesia? Perbankan syariah semakin dituntut untuk mengintegrasikan kepatuhan syariah dan praktik keberlanjutan sebagai bagian dari upaya memperkuat ketahanan jangka panjang. Meskipun demikian, bukti empiris mengenai hubungan antara kinerja berbasis Islamicity, Green Banking, dan stabilitas bank masih menunjukkan hasil yang beragam, khususnya pada sistem keuangan syariah di negara berkembang seperti Indonesia. Penelitian ini menganalisis pengaruh komponen Islamicity Performance Index (IPI) dan praktik Green Banking terhadap stabilitas bank umum syariah di Indonesia selama periode 2021–2024. Studi ini menggunakan data panel seimbang dengan lima dimensi IPI, yaitu Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), Directors–Employees Welfare Ratio (DEWR), serta Islamic Income versus Non-Islamic Income Ratio (IsIR). Analisis dilakukan dengan Moderated Regression Analysis (MRA) menggunakan estimasi pooled panel dan HC3 robust standard errors untuk menguji pengaruh langsung dan efek moderasi. Hasil penelitian menunjukkan bahwa hanya IsIR yang berpengaruh positif signifikan terhadap stabilitas bank, yang mengindikasikan bahwa kemurnian pendapatan halal masih menjadi faktor utama ketahanan perbankan syariah. Sebaliknya, PSR, ZPR, EDR, dan DEWR tidak menunjukkan pengaruh signifikan. Selain itu, Green Banking tidak terbukti memoderasi hubungan antara indikator IPI dan stabilitas bank, yang menunjukkan bahwa praktik keberlanjutan belum terintegrasi secara optimal dalam kinerja syariah inti. Temuan ini memperkaya literatur terkait teori pemangku kepentingan, maqāṣid al-sharīʿah, dan keberlanjutan, sekaligus menegaskan pentingnya penguatan integrasi Sharia–ESG, pengembangan pembiayaan berbasis bagi hasil, serta internalisasi prinsip keberlanjutan dalam strategi perbankan syariah.